Faktor yang Mempengaruhi Keberhasilan Perusahaan Mencapai Peringkat PROPER Emas: Analisis Literatur dan Kebijakan 2020–2025 - Farahiyah Nur Ramadhanty; Muhammad Farid Dimjati Lusno (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
The Corporate Performance Rating Program in Environmental Management (PROPER) is a strategic instrument to encourage industrial environmental performance. Although it has been running for two decades, the achievement of the Gold rating (beyond compliance) remains low. This study aims to identify the factors influencing companies' success in achieving the PROPER Gold rating through a review of national literature and policy documents for the 2020-2025 period. The method used is a systematic literature analysis of 10 research articles and relevant policies. The results show that achieving a Gold rating is influenced by technical factors such as the implementation of Life Cycle Analysis (LCA), consistency in environmental quality monitoring, and the integration of social aspects through Corporate Social Responsibility (CSR). There is also a positive correlation between PROPER ratings and transparency in carbon emission disclosure and profitability, although market responses to company value still vary. The implications of this study emphasize the importance of strengthening incentives for companies and synchronizing policies between central and local governments.